Characterization of Coffee Business Waste in the form of Robusta Coffee Dregs as Adsorbent: A Preliminary Study - Sihombing, Rony; Soeswanto, Bambang; Adhitasari, Alfiana; Yusuf, Yusmardhany; Putri, Alifhah Ananda; Fatah, Khalaida Fania; Clarisa, Shintiya; Gunawan, Sinna Chaerunnabila; Leoanggraini, Unung; Muhari, Emma Hermawati; Kurnia, Dianty Rosirda Dewi (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Robusta coffee grounds are widely produced in several types of businesses, one of which is the coffee industry (coffee shop). This pulp can be reused by business people by being used as an adsorbent and paired with the industrial waste. The purpose of this research is to identify the carbon of Robusta coffee grounds between before and after chemical activation. The methods used were sieving, drying at 25°C to 110°C, carbonization at 600°C, immersion in 0.1M HCl solution. Carbonization of Robusta coffee grounds was carried out using BET, FTIR and SEM. The results showed an increase in carbon surface area from 0.588 m2/g to 14.609 m2/g. The results of the FTIR method showed a change in functional groups on several peaks between pre- and post-activation conditions. The results of the SEM method showed an increase in pore size from 5.5 µm (before activation) to 11 µm (after activation). Keywords: Robusta coffee, Coffee grounds, FTIR, Adsorbent